2016
DOI: 10.1002/jmv.24493
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Aptima® HIV‐1 Quant Dx assay for HIV‐1 RNA viral load detection and quantitation in plasma of HIV‐1‐infected individuals: A comparison with Abbott RealTime HIV‐1 assay

Abstract: The Hologic Aptima ® HIV‐1 Quant Dx assay (Aptima HIV) is a real‐time transcription‐mediated amplification method CE‐approved for use in diagnosis and monitoring of HIV‐1 infection. The analytical performance of this new assay was compared to the FDA‐approved Abbott RealTi m e HIV‐1 (RealTime). The evaluation was performed using 220 clinical plasma samples, the WHO 3rd HIV‐1 International Standard, and the QCMD HIV‐1 RNA EQA. Concordance on qualitative results, cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 36 publications
7
22
0
Order By: Relevance
“…Thus, differences in quantitation between the three assays can be normalized to nearly equivalent levels if the data are expressed in international units, although quantitation of subtypes C, F, and G and CRF02_AG would still be 0.20 to 0.25 log lower by RealTime assay than by Aptima assay. Overall differences in quantitation among the three assays are relatively small and are comparable across diverse group M subtypes, recombinant circulating forms, and group O samples, and the results are consistent with previous studies (30)(31)(32)(33)(34)(35)(36). Our study demonstrates the excellent linearity and accuracy of the Aptima assay in quantifying viral load measurements on diverse HIV-1 subtypes, groups, and circulating recombinant forms, even at very low RNA levels.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Thus, differences in quantitation between the three assays can be normalized to nearly equivalent levels if the data are expressed in international units, although quantitation of subtypes C, F, and G and CRF02_AG would still be 0.20 to 0.25 log lower by RealTime assay than by Aptima assay. Overall differences in quantitation among the three assays are relatively small and are comparable across diverse group M subtypes, recombinant circulating forms, and group O samples, and the results are consistent with previous studies (30)(31)(32)(33)(34)(35)(36). Our study demonstrates the excellent linearity and accuracy of the Aptima assay in quantifying viral load measurements on diverse HIV-1 subtypes, groups, and circulating recombinant forms, even at very low RNA levels.…”
Section: Discussionsupporting
confidence: 89%
“…The modest increase (1.5-to 2-fold) in viral loads observed at concentrations above 10,000 copies/ml of HIV-1 by using the Hologic assay relative to the comparator assays should have a minimal impact on treatment decisions because these concentrations are significantly above the 200-copies/ml medical decision point in the NIH treatment guidelines (2). Studies conducted by various investigators showed that although the Aptima assay detected HIV in more samples, the number of quantified results above 50 copies/ml reported by the Aptima assay was lower than those for the CAP/ CTM and RealTime assays (30)(31)(32)(33). Therefore, the likelihood of a patient categorized as virologically controlled by the CAP/CTM or RealTime assay (below 200 copies/ml) yielding results above the medical decision point (200 copies/ml) in the Aptima assay is low.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…While several studies have compared Aptima to a variety of HIV-1 virus load tests (25,26,(32)(33)(34)(35), to date, only the studies from Hopkins et al (25) and Nair et al (26) have compared Aptima with CAP/CTM. Consistent with the evaluation presented here, in those studies linearity was confirmed using commercially available material, similar levels of precision were observed at low virus loads, and there was good agreement between methods for both qualitative and quantitative results.…”
Section: Discussionmentioning
confidence: 99%
“…Yet another study found Aptima‐HIV‐1 to be more sensitive than CAP/CTM2 . Aptima‐HIV‐1 has also been shown to have performance characteristics similar to or better than the RealTime HIV‐1 assay (Abbott Molecular, Des Plaines, Illinois) and superior to the NucliSens EasyQ HIV‐1 v.2 assay (BioMérieux, Marcy l'Etoile, France) and the Artus HIV‐1 QS‐RGQ assay (Qiagen GmbH, Hilden, Germany) …”
Section: Discussionmentioning
confidence: 99%